PSYCHOLOGICAL PECULIARITIES OF CREATIVE ACTIVITY DEVELOPMENT OF FUTURE PSYCHOLOGISTS - Гоцуляк, Н. (Київський національний університет імені Тараса Шевченка, 2019)
The article is devoted to the study of the psychological peculiarities of the development of creative activity of future psychologists. Creativity as a scientific problem in psychology began to be studied relatively long ago, it is one of the most serious areas of theoretical and experimental study. A creatively active person differs not in the presence of some special, unique qualities, but mainly in the development of those that are necessary for productive activity. It is necessary to take into account that the personality is integral and therefore the predominant development of its individual features can not be accompanied by a qualitative restructuring of the entire structure. Key words: creativity, creative activity, creatively active person, mechanism of creativity, motivational factors, self-education, future psychologists.

Досліджено психологічні особливості розвитку творчої активності майбутніх психологів. Визначено, що творчість як наукова проблема в психології почала вивчатися порівняно давно, це одна з найважливіших сфер теоретичного та експериментального досліджень. Установлено, що творча активність є атрибутивною характеристикою діяльності будь-якої людини, але міра нелінійності та її орієнтація визначаються її індивідуальними психологічними особливостями. Ключові слова: творчість, творча активність, творчо активна людина, механізм творчості, мотиваційні чинники, самоосвіта, майбутні психологи.
ПСИХОЛОГІЧНІ ОСОБЛИВОСТІ РОЗВИТКУ ТВОРЧОЇ ДІЯЛЬНОСТІ МАЙБУТНІХ ПСИХОЛОГІВ